Misuse Of Customer Funds As A Banking Crime In Jayapura City - Nur Asmarani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Misuse of customer deposits as a banking crime is a very worrying and detrimental problem for both customers and the bank concerned. The aim of this research is to analyze, understand and explain that misappropriation of customer deposits is a banking crime and the government should implement a customer deposit guarantee model. The method used is normative and empirical, namely research that examines the literature and applicable laws and regulations using descriptive characteristics, then analyzes it carefully and thoroughly in accordance with the research objectives and looks at the reality that occurs at the research location. The results of the research reveal that misuse of customer deposits by bank leaders, bank employees and stakeholders is a banking crime based on Article 48 paragraph (2) of Law Number 10 of 1998. Legal protection for customers by providing a model implemented by the government to safeguard customer deposits namely the Law on Deposit Insurance Corporation (LPS), Law no. 24 of 2004 which has two functions, namely guaranteeing bank customer deposits and clearing or handling failed deposits as well as synergy between Bank Indonesia and the Financial Services Authority (OJK).